2010
DOI: 10.1186/1741-7015-8-10
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the McKenzie method in addition to first-line care for acute low back pain: a randomized controlled trial

Abstract: BackgroundLow back pain is a highly prevalent and disabling condition worldwide. Clinical guidelines for the management of patients with acute low back pain recommend first-line treatment consisting of advice, reassurance and simple analgesics. Exercise is also commonly prescribed to these patients. The primary aim of this study was to evaluate the short-term effect of adding the McKenzie method to the first-line care of patients with acute low back pain.MethodsA multi-centre randomized controlled trial with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 36 publications
1
74
0
5
Order By: Relevance
“…15,43,44 Apeldoorn et al 44 reported a mean baseline score of 6.06 on the NRS, which was lowered to 4.04 following 8 weeks of treatment with Delitto et al's TBC system. Our mean NRS scores were 3.43 at baseline and 0.23 at discharge, and were achieved within 1 month for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,43,44 Apeldoorn et al 44 reported a mean baseline score of 6.06 on the NRS, which was lowered to 4.04 following 8 weeks of treatment with Delitto et al's TBC system. Our mean NRS scores were 3.43 at baseline and 0.23 at discharge, and were achieved within 1 month for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Individual patient data were extracted from 13 studies previously conducted by the authors or their colleagues between 2001 and 2009 [22][23][24][25][26][27][28][29][30][31][32]. Studies were eligible for inclusion if they contained the ''I sleep less well because of my back'' item of the Roland and Morris Disability Questionnaire (RMDQ).…”
Section: Methodsmentioning
confidence: 99%
“…To harmonise data, responses on this questionnaire were multiplied by 1.67. Two studies [23,30,32] used pain items from the Oswestry [34] and CORE [35] questionnaires and, to harmonise the data, responses were multiplied by 2.…”
Section: Pain Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two RCTs have investigated the effects of the McKenzie method in patients with acute nonspecific LBP who were seeking care from a primary care physician [7,8]. Cherkin et al [7] found that patients randomized to treatment with the McKenzie method had only minimally improved outcomes when compared to those receiving an educational booklet.…”
Section: Introductionmentioning
confidence: 99%